2016
DOI: 10.1016/j.jaad.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and response of patients applying topical therapy for pyoderma gangrenosum: A prospective cohort study

Abstract: BACKGROUND: Pyoderma gangrenosum (PG) is an uncommon dermatosis with a limited evidence base for treatment. OBJECTIVE: We sought to estimate the effectiveness of topical therapies in the treatment of patients with PG. METHODS: This was a prospective cohort study of UK secondary care patients with a clinical diagnosis of PG that was suitable for topical treatment (recruited between July 2009 and June 2012). Participants received topical therapy after normal clinical practice (primarily topical corticosteroids [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 13 publications
2
37
1
Order By: Relevance
“…The most common subtype of PG in our cohort was ulcerative (70%) and the most frequently reported comorbidities were inflammatory bowel disease (IBD) (30%), rheumatoid arthritis (RA) (16%) and diabetes (14%). The mean reported DLQI score was 14·9 ± 8·0, which is at the high end of scores reported in other studies, ranging from 8·4 to 15 . Our high DLQI scores may be partly explained because some of our patients were evaluated at an academic tertiary‐care centre.…”
Section: Summary Of Clinical Features Demographic Data and Quality‐omentioning
confidence: 47%
“…The most common subtype of PG in our cohort was ulcerative (70%) and the most frequently reported comorbidities were inflammatory bowel disease (IBD) (30%), rheumatoid arthritis (RA) (16%) and diabetes (14%). The mean reported DLQI score was 14·9 ± 8·0, which is at the high end of scores reported in other studies, ranging from 8·4 to 15 . Our high DLQI scores may be partly explained because some of our patients were evaluated at an academic tertiary‐care centre.…”
Section: Summary Of Clinical Features Demographic Data and Quality‐omentioning
confidence: 47%
“…A parallel observational study showed that topical therapy is potentially an effective first‐line treatment for smaller PG ulcers, avoiding possible side‐effects of systemic therapy . However, the average ulcer size in these participants was only about half that of the participants in the main RCT, so it remains unclear whether more severe disease will respond adequately to topical therapy alone.…”
Section: What Were the Main Results Of The Stop Gap Trial?mentioning
confidence: 99%
“…Nevertheless, localised and mild PG may be effectively controlled using topical agents without incurring the side effects associated with systemic treatments. In most cases, the preference is for corticosteroids and calcineurin inhibitors 2 3…”
Section: Discussionmentioning
confidence: 99%